The Relationship of Delayed Appendectomy to the Incidence of Surgical Site Infection (SSI) in Acute Appendicitis Patients: A Narrative Review - Wahyuning Ati Ashari; Enny Suswati; Erfan Efendi (Media Penelitian dan Pengembangan Kesehatan, 2021)
Acute appendicitis is one of the most common causes of surgery worldwide. Appendectomy is a skeptical surgical intervention associated with the risk of Surgical Site Infection (SSI). The purpose of this analysis was to describe the relationship between delayed appendectomy in acute appendicitis and the incidence of SSI. Reviewers selected articles containing data on the incidence of SSI due to appendectomy delays for 3 to 48 hours from seven databases, namely Pubmed, Nature, SpringerLink, Science Direct, ProQuest, Oxford Open Access Journal, and Cochrane Library. The data source was secondary data from international articles published in 2011 to 2020 based on the PICO criteria. The data obtained were then grouped and synthesized without meta-analysis/Synthesis Without Metaanalysis (SWiM) descriptively. A total of 2,778 articles were collected, of which 24 studies met the inclusion criteria. A total of 4 articles showed an association between appendectomy delay and SSI while the other 20 articles did not show a relationship between the two. There was no relationship between appendectomy delays for less than 48 hours since hospital admission to surgery with the incidence of SSI, however a delayed for more than 48 hours showed a significant value. The results showed there was no relationship between delayed appendectomy for less than 48 hours since the time the patientwas admitted to the hospital until the surgery took place, but a delayed appendectomy delay for more than 48 hours showed a significant relationship with the incidence of SSI. This narrative review supports early surgical intervention of acute appendicitis cases by considering the severity of the patient to avoid other surgical complications. Abstrak Apendisitis akut menjadi salah satu penyebab pembedahan yang paling sering ditemukan di seluruh dunia. Apendektomi merupakan intervensi bedah skeptis yang berhubungan dengan risiko terjadinya Surgical Site Infection (SSI). Tujuan analisis ini untuk mendapatkan gambaran hubungan antara penundaan apendektomi pada apendisitis akut dengan kejadian SSI. Reviewer memilih artikel yang memuat data kejadian SSI akibat penundaan apendektomi selama 3 sampai 48 jam dari tujuh basis data yaitu Pubmed, Nature, SpringerLink, Science Direct, ProQuest, Oxford Open Access Journal, dan Cochrane Library. Sumber data berupa data sekunder dari artikel internasional yang diterbitkan pada tahun 2011 hingga 2020 berdasarkan kriteria PICO. Data yang didapatkan kemudian dikelompokkan dan disintesis tanpa meta-analisis/Synthesis Without Meta-analysis (SWiM) secara deskriptif. Total artikel yang dikumpulkan adalah 2.778 artikel, sebanyak 24 studi memenuhi kriteria inklusi. Sebanyak 4 artikel menunjukkan hubungan antara keterlambatan apendektomi dengan SSI sedangkan 20 artikel lainnya tidak menunjukkan hubungan keduanya.Tidak ada hubungan penundaan apendektomi kurang dari 48 jam sejak masuk rumah sakit hingga operasi dengan insidensi SSI namun penundaan lebih dari 48 jam menunjukkan nilai yang signifikan. Berdasarkan hasil analisis, disimpulkan bahwa tidak terdapat hubungan penundaan apendektomi selama kurang dari 48 jam sejak pasien masuk rumah sakit hingga proses pembedahan berlangsung tetapi penundaan apendektomi lebih dari 48 jam menunjukkan adanya hubungan signifikan terhadap kejadian SSI. Tinjauan naratif ini mendukung intervensi bedah yang cepat pada kasus apendisitis akut dengan mempertimbangkan tingkat keparahan pasien dan untuk menghindari komplikasi pembedahan lain.